Virtual reality applications in the extractive industrya short review - Joana Duarte (2019)
The mining industry presents itself as one of the sectors with major occupational accidents, being only surpassed by agriculture (including fishing) and forestry (including hunting). The technology development has been improving safety awareness and working practises; one of the most used tools is virtual reality (VR). The PRISMA Statement methodology was applied in order to find evidence of these new technologies in the extractive industry. For that, a set of keywords related to both topics (mining and VR) was defined, and the main journals and databases in the engineering field were screened. After applied both exclusion and inclusion criteria, the 1786 papers were reduced to eight. The results show that this resource is useful, however, when comparing to the application in the construction field, in what concerns to safety management, there is still a lot to achieve. (c) Springer Nature Switzerland AG 2019.